Plant responses to soil heterogeneity and global environmental change - García-Palacios, Pablo (J Ecol, 2012)
1. Recent evidence suggests that soil nutrient heterogeneity, a ubiquitous feature of terrestrial ecosystems, modulates plant responses to ongoing global change (GC). However, we know little about the overall trends of such responses, the GC drivers involved, and the plant attributes affected. 2. We synthesized literature to answer the question: Does soil heterogeneity significantly affect plant responses to main GC drivers, such as elevated atmospheric carbon dioxide concentration (CO(2)), nitrogen (N) enrichment and changes in rainfall regime? 3. Overall, most studies have addressed short-term effects of N enrichment on the performance of model plant communities using experiments conducted under controlled conditions. The role of soil heterogeneity as a modulator of plant responses to elevated CO(2) may depend on the plasticity in nutrient uptake patterns. Soil heterogeneity does interact with N enrichment to determine plant growth and nutrient status, but the outcome of this interaction has been found to be both synergistic and inhibitory. The very few studies published on interactive effects of soil heterogeneity and changes in rainfall regime prevented us from identifying any general pattern. 4. We identify the long-term consequences of soil heterogeneity on plant community dynamics in the field, and the ecosystem level responses of the soil heterogeneity × GC driver interaction, as the main knowledge gaps in this area of research. 5. In order to fill these gaps and take soil heterogeneity and GC research a step forward, we propose the following research guidelines: 1) combining morphological and physiological plant responses to soil heterogeneity with field observations of community composition and predictions from simulation models; and 2) incorporating soil heterogeneity into a trait-based response-effect framework, where plant resource-use traits are used as both response variables to this heterogeneity and GC, and predictors of ecosystem functioning. 6. Synthesis. There is enough evidence to affirm that soil heterogeneity modulates plant responses to elevated atmospheric CO(2) and N enrichment. Our synthesis indicates that we must explicitly consider soil heterogeneity to accurately predict plant responses to GC drivers.